PENINGKATAN KEPUASAN PELANGGAN MCD DRIVE THRU KENDARI MELALUI VARIASI PRODUK DAN KUALITAS LAYANAN - Harmi, Harmi; Juharsah, Juharsah; Rommy, Nursaban; Hartini, Hartini; Nur, Noval (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2024)
This research aims: 1. To determine the increase in customer satisfaction at Mcd Drive Thru Kendari through product variations and service quality. 2. To determine the increase in customer satisfaction at Mcd Drive Thru Kendari through product variations. 3. To determine the increase in customer satisfaction at Mcd Drive Thru Kendari through Service Quality. The total population in this study was 96 respondents. This research uses multiple linear regression analysis.The research results show that: 1. Mcd Drive Thru Kendari customer satisfaction can increase through product variations and service quality. 2. Mcd Drive Thru Kendari customer satisfaction can be increased through product variations. 3. Mcd Drive Thru Kendari customer satisfaction can be improved through service quality.